1993
DOI: 10.1002/ijc.2910530115
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical study of c‐erbb‐2 protein in gastric carcinomas and lymph‐node metastases: Is the c‐erbB‐2 protein really a prognostic indicator?

Abstract: An immunohistochemical study of the c-erbB-2 protein was conducted on formalin-fixed paraffin-embedded tissue sections from 136 primary gastric carcinomas and 50 metastatic lymph-node tumors obtained at gastrectomy. Expression of the protein was detected in 35 of 136 primary gastric carcinomas (25.7%) and 22 of 50 metastatic lymph nodes (44%). The staining pattern of tumor cells was classified as membranous or cytoplasmic. An immunohistochemical study using serially diluted antibody demonstrated that 82.6% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 26 publications
1
11
0
1
Order By: Relevance
“…Various studies have not revealed an association of the c-ErbB-2 expression and prognosis in gastric cancer [25,26]. In our immunohistochemical study, c-ErbB-2 protein overexpression in patients with gastric carcinomas who received curative surgery had a tendency to a poor prog nosis.…”
Section: Discussionmentioning
confidence: 68%
“…Various studies have not revealed an association of the c-ErbB-2 expression and prognosis in gastric cancer [25,26]. In our immunohistochemical study, c-ErbB-2 protein overexpression in patients with gastric carcinomas who received curative surgery had a tendency to a poor prog nosis.…”
Section: Discussionmentioning
confidence: 68%
“…The type of cytoplasmic staining could be classified as diffuse and granular. Diffuse cytoplasmic staining without membranous staining was noted in cases of gastric carcinoma [25], adenocarcinoma of the uterine cervix [27] and adenocarcinoma of Barrett's esophagus [28]. Granular cytoplasmic staining was seen in cases of breast carcinoma [21] and gastric carcinoma [10].…”
Section: Discussionmentioning
confidence: 96%
“…Eighteen of 93 patients with gastric cancer (19%) had HER-2/neu overexpression, which was in line with previous reports. 10,19,22,23 The frequency of HER-2/neu overexpression in the carcinoma tissue of HLA-A2-positive and negative patients was almost equal at 20% and 19%, respectively. Moreover, there were no significant differences in the frequency of HER-2/neu status related to HLA-A11, A24, A26, B51 or Cw3 loci.…”
Section: Frequency Of Hla Haplotype Related To Her-2/neu Overexpressionmentioning
confidence: 97%